The Stability of a General Sextic Functional Equation by Fixed Point Theory - Jaiok Roh; Yang-Hi Lee; Soon-Mo Jung (Journal of Function Spaces)
In this paper, we will consider the generalized sextic functional equation ∑i=07 7Ci−17−ifx+iy=0. And by applying the fixed point theorem in the sense of Ca˘dariu and Radu, we will discuss the stability of the solutions for this functional equation.